Pengaruh Profitabilitas, Struktur Kepemilikan, Tingkat Pertumbuhan Perusahaan dan Efektifitas Usaha terhadap Kebijakan Deviden - Galih Sanjaya; Nurdhiana Nurdhiana; Yeni Kuntari (Jurnal Ilmiah Aset, 2018)
This research aimed to find out the influence of profitability, ownership structure, growth, and business effectiveness on dividend policy. The population in thisresearch were manufacturing companies listed in BEI as many as 419 companies, while the sample used as many as 18 companies. The sampling technique used was non probability purposive sampling judgment. The analysis tool used was multiple linear regression, besides also tested classical assumption. The results showed profitability, growth rate and effectiveness of business had significant positive effect on dividend policy, ownership structure had significant negative effect on dividend policy. Based on the results of research profitability, ownership structure, growth, and effectiveness of business may explain thedividend policy as high as 91.5% while the rest of 8.5% are explained by other variables not included in the research.